2014
DOI: 10.1074/jbc.m114.586537
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray Structure of NccX from Cupriavidus metallidurans 31A Illustrates Potential Dangers of Detergent Solubilization When Generating and Interpreting Crystal Structures of Membrane Proteins

Abstract: Background: NccX is the membrane-anchored periplasmic metal sensor of the NccYXH transmembrane signal transduction complex. Results: Detergent-induced redistribution of the hydrophobic interactions led to a non-native x-ray structure. Conclusion: Molecular dynamics simulations along with in vivo assays reconciled the structural data with a physiological model of NccX dimer. Significance: Complementary investigations are needed to rationalize three-dimensional structures obtained in non-native conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…B. Model of the transmembrane domain of L. monocytogenes PgdA (residues 3–25) obtained with SWISS MODEL (Biasini et al ., ) on the nickel‐cobalt‐cadmium resistance protein NccX from Cupriavidus metallidurans as template (Ziani et al ., ). Residues contributing to PBP A1 binding (red) and PgdA dimerization (blue) are shown.…”
Section: Resultsmentioning
confidence: 98%
“…B. Model of the transmembrane domain of L. monocytogenes PgdA (residues 3–25) obtained with SWISS MODEL (Biasini et al ., ) on the nickel‐cobalt‐cadmium resistance protein NccX from Cupriavidus metallidurans as template (Ziani et al ., ). Residues contributing to PBP A1 binding (red) and PgdA dimerization (blue) are shown.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, recent work on the CnrX-homologue NccX has shown that these coalesced hydrophobic cores determine the dimerization of the full length, membrane-embedded protein as well. 46 Central in the CnrX protomer architecture is M123 that lies at the bottom of the cavity that harbors the metal ion. This residue is also crucial for the signaling mechanism as its recruitment in the coordination sphere of Ni(II) or Co(II) is the key event that initiates the biological response.…”
Section: Discussionmentioning
confidence: 99%
“…Events downstream metal sensing by CnrX remains to be investigated. Recent in vivo and in silico data have shown that the transmembrane segments of isolated NccX, a close CnrX homologue, engage in highly dynamic self-interactions, 46 which indicates that they might not support signaling on their own. The characterization of the interaction between CnrH and CnrY cytosolic domain also suggested that CnrY would probably not propagate a conformational change.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting case is the protein NccX, 359 of which a crystal structure has been determined in DPC. Intriguingly, “the periplasmic domains of NccX appeared collapsed against the hydrophobic TM segments, leading to an aberrant topology incompatible with membrane insertion.” The authors explained this unusual topology with a “detergent-induced redistribution of the hydrophobic interactions among the TM helices and a pair of hydrophobic patches keeping the periplasmic domains together in the native dimer.” In this case, alkyl phosphocholine led to a very unusual architecture that does not seem to be of biological relevance.…”
Section: Studies Of Mps In Dpc Reveal Strengths and Weaknessesmentioning
confidence: 99%
“…Monomeric single-span TM helices may not be impacted by these considerations, and in alkyl phosphocholine they may largely retain their structural properties (see the discussion on simulations of TM peptides in section 5 and references therein). This being said, the cases of NccX 359 and Rv1761c 358 show that also single-span helices may be significantly impacted in alkyl phosphocholine in terms of dimerization or local structure; the presence of hydrophilic or traditional helix breaking residues such as proline and glycine has led to an unphysiological structure in the latter case. Thus, even in single-span TM proteins, one needs to be cautious when interpreting structural data.…”
Section: Studies Of Mps In Dpc Reveal Strengths and Weaknessesmentioning
confidence: 99%